2021
DOI: 10.1093/mnras/stab943
|View full text |Cite
|
Sign up to set email alerts
|

Three ultraluminous X-ray sources hosted by globular clusters in NGC 1316

Abstract: We have identified three ultraluminous X-ray sources (ULXs) hosted by globular clusters (GCs) within NGC 1316’s stellar system. These discoveries bring the total number of known ULXs in GCs up to 20. We find that the X-ray spectra of the three new sources do not deviate from the established pattern of spectral behaviour of the other known GC ULXs. The consistency of the X-ray spectral behaviour for these sources points to multiple paths of formation and evolution mechanisms for these rare and unique sources. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…X-ray variability is another key diagnostic in the study of extragalactic X-ray binaries. Previous studies of GCULXs have identified several different behaviours, with nine showing no variability within an observation or across many years of observations Dage et al (2019aDage et al ( , 2020Dage et al ( , 2021, eight that vary over the course of many observations, but not within an observation Dage et al (2019aDage et al ( , 2020, and three that vary within an observation (Maccarone et al 2007;Shih et al 2010;Dage et al 2020). Variability is also seen in ULXs in star-forming galaxies, e.g.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…X-ray variability is another key diagnostic in the study of extragalactic X-ray binaries. Previous studies of GCULXs have identified several different behaviours, with nine showing no variability within an observation or across many years of observations Dage et al (2019aDage et al ( , 2020Dage et al ( , 2021, eight that vary over the course of many observations, but not within an observation Dage et al (2019aDage et al ( , 2020, and three that vary within an observation (Maccarone et al 2007;Shih et al 2010;Dage et al 2020). Variability is also seen in ULXs in star-forming galaxies, e.g.…”
Section: Introductionmentioning
confidence: 96%
“…A large number of ULXs are formed in the star forming regions of spiral galaxies (Swartz et al 2009). However, a growing number of ULXs have been discovered in a very different stellar and dynamical environment, the globular clusters associated with early type galaxies (Dage et al 2019a(Dage et al , 2020(Dage et al , 2021. Because these ULXs are born in old and dynamic globular cluster systems, they are low mass X-ray binary (LMXB) ULXs, and undergo quite different for-★ E-mail: athukora@msu.edu mation mechanisms than their star-forming contemporaries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCs are also known to host a variety of X-ray sources and radio transients. These include ultra-luminous X-ray sources (ULXs) which undergo some of the most extreme mass transfer rates, and may also be indicators of BH candidates in extragalactic globular clusters (Dage et al 2021, and references therein). X-ray sources have also been traced back to ultracompact dwarf (UCD) hosts (e.g., Seth et al 2014;Pandya et al 2016), of which there are many theories regarding their definition, make-up, and origin -one common theory being that UCDs are primarily the nuclei of tidally stripped dwarf galaxies (Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A survey by Swartz et al (2009) shows that ULXs are mainly associated with the star-forming regions of galaxies. Elliptical galaxies are known to host off-centre ULXs, but those are associated with globular clusters Dage et al (2021). Thus, the identification and detailed study of ULXs that are neither hosted by globular clusters, nor associated with the star-forming regions of the galaxies, provides a different angle on ULX systems.…”
Section: Introductionmentioning
confidence: 99%